RANCANG BANGUN SISTEM KENDALI ROBOT LENGAN 6 DERAJAT KEBEBASAN BERBASIS INTENET OF THINGS - Eliyana Firmansya; Syahban Rangkuti; Andri Fitriyadi (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2024)
Abstract — Robotics technology has developed very rapidly at this time. Various advanced technologies have replaced manual equipment that requires a lot of human power to operate, one of which is using robots. In this research, a robot arm control system with 6 degrees of freedom will be designed. There are many applications or applications of this robotic arm in the industrial world, including moving goods to places that are dangerous or cannot be entered by humans. The 6 degrees of freedom robot arm uses two servo motor units and 4 DC motor units as its driving force, where all the motors used can move individually or simultaneously. In order to be able to move the robot arm according to the commands given, various electronic devices are needed, including a DC motor drive module type L298N motor driver, an Arduino Mega 2560 microcontroller module to move the motor the commands received, and an ESP8266 NodeMCU which functions as data communication using technology internet of things. This robot arm can be controlled using a smartphone or computer via an application that has been built into it. The data communication that will be used to apply internet of things technology to the robot arm control system is the MQTT protocol. By using the MQTT protocol, control systems can be developed easily using a web server application.